Observation of Electroweak Production of a Same-Sign W Boson Pair in Association with Two Jets in pp Collisions at sqrt[s]=13 TeV with the ATLAS Detector - Çetin, Serkant Ali (Amer. Physical Soc., 2019)
This Letter presents the observation and measurement of electroweak production of a same-sign W boson pair in association with two jets using 36.1 fb(-1) of proton-proton collision data recorded at a centerof-mass energy root s = 13 TeV by the ATLAS detector at the Large Hadron Collider. The analysis is performed in the detector fiducial phase-space region, defined by the presence of two same-sign leptons, electron or muon, and at least two jets with a large invariant mass and rapidity difference. A total of 122 candidate events are observed for a background expectation of 69 +/- 7 events, corresponding to an observed signal significance of 6.5 standard deviations. The measured fiducial signal cross section is sigma(fid) = 2.89(-0.48)(+0.51)(stat)(-0.28)(+0.29)(syst) fb.
Keywords: weak-interactions; high-energies; syststem